The Potiguar Eddy: a subsurface anticyclone associated with the North Brazil Undercurrent at 4ºS - Krelling, Ana Paula Morais (2015)
In this dissertation we describe a newly discovered subsurface frontal meander of the North Brazil Undercurrent (NBUC), centered at about 4ºS, 36.5ºW, hereafter Potiguar Eddy (PE). The Potiguar Eddy is an elliptically-shaped eddy, with major and minor axes of approximately 330 and 130 km, with a subsurface signature. It extends vertically from 100 m to 400 m, with maximum velocities of 0.6 m.s-1 and recirculates about 2 Sv of waters from the NBUC. Despite the presence of the PE in subtermocline waters, the surface flow is northwestward throughout the year. The analysis of variability of mooring velocity data in the Potiguar Bight revealed two most important statistical modes of variability (EOFs); one with high amplitudes over most of the portion of the water column which corresponds to the PE, and another one, explaining a lower percentage of the variance, associated with upper-layer processes. The first EOF mode is found to be associated with baroclinic oscillations with periods of about 25-35 days. This signal is also seen in altimetric fields in the Atlantic Ocean. We characterize these signals as Rossby waves, and speculate that the trigger for their generation would be barotropic instability generated by the current shear in the Tropical Atlantic Ocean. Aditionally, with the intent of analyzing the generation process of the PE, we developed Feature Models of the NBUC and Deep Western Boundary Current (DWBC), to be used as basis for developing the initial field for numerical model simulations in a dynamical process-study approach. The Feature Models, developed from observed velocity data, with temperature calculated through the thermal wind equation, and salinity from WOA (2013) climatology, successfully capture the main attributes of the features of interest, and thus are suitable for the investigation of the main characteristics of the flow in the Potiguar Bight. Two numerical experiments were set up; (i) a NBUC-only experiment, with maximum depth of 1500 m, and (ii) a NBUC-DWBC experiment, with a maximum depth of 5500 m. The Potiguar Eddy was formed in both experiments, with maximum velocity, core depth and size consistent with synoptic observations. As a result, the PE can be generated by a velocity field containing only the NBUC; and the DWBC - induced vertical shear seems to play a part on the eddy\'s characteristics (vertical extent, maximum velocities, etc), since the PE had different formation processes in the two experiments.